The Potential Application of Human Gingival Fibroblast-Conditioned Media in Pulp Regeneration: An In Vitro Study - Huong Thu Vu; Ji-Young Yoon; Jae-Hee Park; Hae-Hyoung Lee; Khandmaa Dashnyam; Hae-Won Kim; Jung-Hwan Lee; Ji-Sun Shin; Jong-Bin Kim (Cells, 2022)
Regenerative endodontic treatment based on tissue engineering has recently gained interest in contemporary restorative dentistry. However, low survival rates and poor potential differentiation of stem cells could undermine the success rate of pulp regenerative therapy. Human gingival fibroblast-conditioned medium (hGF-CM) has been considered a potential therapy for tissue regeneration due to its stability in maintaining multiple factors essential for tissue regeneration compared to live cell transplantation. This study aimed to investigate the potency of hGF-CM on stem cells from human dental pulp (DPSC) in pulp regeneration. A series of experiments confirmed that hGF-CM contributes to a significant increase in proliferation, migration capability, and cell viability of DPSC after H2O2 exposure. Moreover, it has been proved to facilitate the odontogenic differentiation of DPSC via qRT-PCR, ALP (alkaline phosphatase), and ARS (Alizarin Red S) staining. It has been discovered that such highly upregulated odontogenesis is related to certain types of ECM proteins (collagen and laminin) from hGF-CM via proteomics. In addition, it is found that the ERK pathway is a key mechanism via inhibition assay based on RNA-seq result. These findings demonstrate that hGF-CM could be beneficial biomolecules for pulp regeneration.